2011
DOI: 10.4028/www.scientific.net/kem.471-472.513
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behaviour of Polypropylene/Kenaf Fibre Composite: Effect of Fibre Size

Abstract: In evaluating thermoplastics for their effective performance during processing, rheology properties are very useful. Similarly, in designing processing apparatus, knowledge of rheological behavior of composite melt is critical. In this study, melt flow and viscosity behavior of polypropylene/kenaf fibre composite was investigated using a single-screw extruder. Subsequently, flow behavior of the compounded formulation were evaluated by comparing the melt flow index, flow curve and viscosity curve of the PP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Ersoy and Taşdemir ( 2012 ) indicated a more than 52.22 % decline of MFR from 0 to 20 wt% of MH filled composites. By increasing the MH content from 5 to 10 wt% (sample 4–5), the MH particles formed new network junctions in the composites, resulting in better interaction forces and friction forces (Crowson et al 1980 ; Khalina et al 2011 ). Therefore lower MVR and MFR values for the composites were found with increasing MH contents (Liang et al 2000 ).…”
Section: Results Sectionmentioning
confidence: 99%
“…Ersoy and Taşdemir ( 2012 ) indicated a more than 52.22 % decline of MFR from 0 to 20 wt% of MH filled composites. By increasing the MH content from 5 to 10 wt% (sample 4–5), the MH particles formed new network junctions in the composites, resulting in better interaction forces and friction forces (Crowson et al 1980 ; Khalina et al 2011 ). Therefore lower MVR and MFR values for the composites were found with increasing MH contents (Liang et al 2000 ).…”
Section: Results Sectionmentioning
confidence: 99%
“…In Malaysia, KNF crops have been planted in large numbers to replace tobacco and are widely studied to sustain the development of new applications of KNF crops . There are numerous studies on (KNF fiber)‐filled polymer composites being investigated and reported . The utilization of KNF fiber in polymer composites applications can help in solving waste management on disposal, hence protecting the environment.…”
Section: Introductionmentioning
confidence: 99%
“…KNF is a low cost, renewable, and quick growing annual plant, which is used extensively as a filler in polymer composites . For instance, Ismail et al used KNF core fiber as a filler in high‐density polyethylene/soya powder composites and found that the tensile modulus, flexural strength, and flexural modulus of the composites increased with the addition of KNF core.…”
Section: Introductionmentioning
confidence: 99%